2009
DOI: 10.1093/eurpub/ckp075
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of varenicline compared with nicotine patches for smoking cessation—results from four European countries

Abstract: This cost-effectiveness analysis demonstrated that since varenicline treatment was more effective, the result was increased healthcare cost savings in Belgium, Sweden and the UK. Our results suggest that funding varenicline as a smoking cessation aid is justifiable from a healthcare resource allocation perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 23 publications
2
65
1
4
Order By: Relevance
“…A significant part of the intervention was smoking cessation programmes, either pharmacotherapy 4, 5, 36, 37, 38, 40, 41, 48, 50, 51, 53, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, behavioural therapy 6, 42, 47, 66, 67, 68, 69 or a combination of these 33, 34, 35, 43, 45, 46, 49, 52, 54, 70, 71, 72, 73, 74, 75. Several studies evaluated wider tobacco control interventions 39, 44, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, whereas five studies included both smoking cessation programmes and tobacco control interventions 89, 90, 91, 92, 93.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant part of the intervention was smoking cessation programmes, either pharmacotherapy 4, 5, 36, 37, 38, 40, 41, 48, 50, 51, 53, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, behavioural therapy 6, 42, 47, 66, 67, 68, 69 or a combination of these 33, 34, 35, 43, 45, 46, 49, 52, 54, 70, 71, 72, 73, 74, 75. Several studies evaluated wider tobacco control interventions 39, 44, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, whereas five studies included both smoking cessation programmes and tobacco control interventions 89, 90, 91, 92, 93.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 23 of 64 studies reported QALY as their main outcome 5, 35, 38, 40, 41, 47, 48, 49, 56, 58, 59, 61, 62, 63, 65, 69, 70, 76, 78, 81, 86, 88, 94, followed by life years (LY) gained ( n  = nine of 64) 33, 43, 46, 66, 67, 68, 73, 74, 89 or a combination of these ( n  = 12 of 64) 4, 6, 35, 36, 37, 39, 42, 44, 57, 77, 80, 83. Five of 64 studies reported disability adjusted life years (DALY) as their main outcome 60, 82, 90, 91, 92, and only four of 64 (incremental) net benefit 52, 53, 55, 71.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BENESCO model has been used in numerous previous evaluations. [63][64][65][66][67][68][69][70][71][72][73] The model uses an annual cycle length and assumes that all smokers die at age 100 years, if death has not been simulated at an earlier age. A hypothetical cohort of 10,000 smokers enters the model, with each smoker assumed to make a single quit attempt, assisted by either varenicline or cytisine.…”
Section: The Conceptual Modelmentioning
confidence: 99%
“…This study compared smoking-related morbidity and mortality and the quality of the adjusted life-years gained and found varenicline to be more cost-effective than NRT. 36 Varenicline was also found to be more cost-effective and cost-saving compared to other smoking cessation treatments such as bupropion and nortriptyline. 4 Varenicline in the family practice setting…”
Section: Special Precaution In Patients With Mental Health Problemsmentioning
confidence: 99%